Instituto de Ciencia Animal: fifty years of scientific research at the service of beef production in Cuba - Rodríguez, Duniesky (Cuban Journal of Agricultural Science, 2016)
This study presents the main scientific results of beef production,obtained in the Instituto de Ciencia Animal, mainly related to the use of grasses, forages and agro-industrial residues, as sources of animal food. The essential elements for a good development of feeding systems are reported. This research also states the knowledge related to stocking rate, grazing methods, supplementation level, and other indicators that allow to optimize each fattening system, with possibilities of obtaining gains near to the kilogram liveweight per day in systems in which the use of oleaginous seeds and cereals only contribute to complement nutritional deficiencies. Key words: feeding, management, fattening, bovine